2012
DOI: 10.1007/s13213-012-0469-9
|View full text |Cite
|
Sign up to set email alerts
|

Culturable actinomycetes from desert ecosystem in northeast of Qinghai-Tibet Plateau

Abstract: In this study, 53 actinomycetes strains were isolated from desert ecosystems located in northeast of Qinghai-Tibet Plateau and grouped into four RFLP patterns. Twenty-six actinomycetes with obvious morphology differences were chosen for phylogenetic diversity study and antimicrobial testing. As a result, the 16S rRNA gene sequencing showed that these strains belonged to Streptomyces, Micromonospora, Saccharothrix, Streptosporangium and Cellulomonas, and that most of the strains had antimicrobial bioactivity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
4
18
1
Order By: Relevance
“…BLAST search results implied that these 41 isolates belonged to the genus Streptomyces (33 isolates), Nocardia (7 isolates) and Kribbella (1 isolate). From the sequencing result, it was clear that Streptomyces was found to be the dominant genus in the soil of protected forest ecosystems which was also reported previously 12,19,70,71 .…”
Section: Discussionsupporting
confidence: 82%
“…BLAST search results implied that these 41 isolates belonged to the genus Streptomyces (33 isolates), Nocardia (7 isolates) and Kribbella (1 isolate). From the sequencing result, it was clear that Streptomyces was found to be the dominant genus in the soil of protected forest ecosystems which was also reported previously 12,19,70,71 .…”
Section: Discussionsupporting
confidence: 82%
“…315 from Mongolian desert soil (Kurapova et al, 2012 ). In addition to Streptomyces , strains belonging to Micromonospora, Saccharothrix, Streptosporangium , and Cellulomonas were obtained from the Qinghai-Tibet Plateau (Ding et al, 2013a ), while Micromonospora, Actinomadura , and Nocardiopsis were reported from soda saline soils of the ephemeral salty lakes in Buryatiya (Lubsanova et al, 2014 ).…”
Section: Xerophilic Strains Isolated From Arid Areasmentioning
confidence: 99%
“…In another study, 53 Actinobacteria isolated from the Qinghai-Tibet Plateau were grouped into four RFLP patterns and identified as Streptomyces, Micromonospora, Saccharothrix, Streptosporangium , and Cellulomonas . Most of these strains had the potential to produce active compounds in addition to the detection of NRPS, PKS-I, and PKS-II genes (Ding et al, 2013a ). Hence, the metagenomic analysis of the bioactive secondary metabolites (Schofield and Sherman, 2013 ; Wilson and Piel, 2013 ) can also be assessed in the future, in order to distinguish the chemical potential of drought adapted Actinobacteria and their conserved secondary metabolites biosynthetic pathways.…”
Section: Biologically Active Metabolites Reported From Xerophilic mentioning
confidence: 99%
“…Micromonosporae have been isolated from diverse natural habitats (Genilloud 2012), notably from rhizosphere soil (Carro et al 2013b;Thawai et al 2016) from desert locations in China (Ding et al .2013) and from tissues of a broad range of plants, such as Triticum aestivum (Coombs and Franco 2003), Zea mays (Shen et al 2014), and Parathelypteris beddomei (Zhao et al 2017); as well as from nitrogen-fixing root nodules of actinorhizal plants (Trujillo et al 2006;Carro et al 2013a) and legumes (Trujillo et al 2007;Garcia et al 2010;Trujillo et al 2010;Carro et al 2018b).…”
Section: Introductionmentioning
confidence: 99%